Internet of Things New Trends, Challenges and Hurdles - Domínguez-Morales, Manuel; Varela-Vaca, Ángel; Miró-Amarante, Lourdes (IntechOpen, 2023)
The Internet of Things (IoT) has emerged as a popular area of research and has piqued the interest of academics and scholars worldwide. As such, many works have been done on IoT in a variety of application areas. Written by leading experts in the field, this book serves as a showcase of the breadth of IoT research conducted in recent years for people who, while not experts in the field, do have prior knowledge of the IoT. The book also serves curious, non-technical readers, enabling them to understand necessary concepts and terminologies associated with the IoT.